Standardisasi Waktu Kerja Pada Unit Pengolahan Kakao, Koperasi Rimbun, Pidie Jaya - Juanda Juanda; Zalniati Fonna Rozali; Hanif Syahputra (Department of Agricultural Engineering, Syiah Kuala University, 2012)
Standardization of Working Time at Cocoa Processing Unit, Rimbun Cooperative, Pidie JayaABSTRACT. Rimbun Cooperative is a business unit operating a chocolate factory producing several chocolate products such as cocoa fat, cocoa powder, 3 in 1 instant drinks (sachets), and chocolate bars. This research aims to measure standard times of operators in all working stations of the chocolate factory. These standards comprised the standards in roasting, peeling, pasting, pressing, powdering, powder sieving, powder mixing, dough mixing, refining, and chonching working stations. The data were directly collected using Time Study method with Stop Watch. The samples were randomly selected with five (5) repetitions; and the standard times were measured using Westinghouse Method to quantify performance and allowance factors. The result shows that standard times of operators in each working station are as follows: roasting (36 minutes), peeling (193 minutes), pasting (276 minutes), pressing (78 minutes), powdering (17 minutes), powder sieving (14 minutes), powder mixing (36 minutes), dough mixing (17 minutes), refining (30 minutes), and chonching (30 minutes). In peeling, pasting, powdering, powder sieving working stations, standard times of operators cannot be separated with working times of machines because the operators are required to run the machines (sequence). In general, standard times of operators, after calculation, are larger than direct records because during the working times, operators would not or could not use allowance factors for personal uses, such as for going to bathroom, drinking, and socializing with their colleagues as means to reduce stress or boredom.